A new Vegetation Integrity metric for trading losses and gains in terrestrial biodiversity value. (May 2021) - Oliver, Ian; Dorrough, Josh; Seidel, John
Highlights: The metric quantifies loss at development sites and predicts gain at offset sites. Its relationship to biodiversity value is explicitly defined and therefore falsifiable. Quantitative features of the metric improve its practical and theoretical properties. The prediction of gain is explicit so that empirical data can test predictions. Abstract: The Vegetation Integrity metric has been designed within a clear management and decision-making context: to quantify losses and predict gains in terrestrial biodiversity value at development and offset sites. The metric incorporates a number of key developments that differentiate it from others. Firstly, the intent is explicitly defined and therefore falsifiable: scores have a positive relationship with the species richness and/or abundance of native plants and animals at sites within the same vegetation type. This relationship is posited because the metric is constructed from a practical set of habitat attributes representative of biodiversity composition, structure and function with known relationships with species occurrence. Secondly, the quantitative features of the metric improve both its practical and theoretical properties. These features include: normalisation of attribute scores by reference to best-on-offer benchmarks that account for inherent differences in attribute abundance among vegetation types; dynamic weighting of attributes to accommodate differences in relative abundance of attributes within vegetation types; attribute scoring using a non-linear continuous function to better represent metric intent and avoid exacerbation of measurement error; and aggregation of composition, structure and function scores using the geometric mean to reduce substitution effects. Thirdly, the prediction of gain in biodiversity value at offset sites is explicit with: attribute-specific probabilistic estimates of reaching best-on-offer benchmark status over 20 years with the management of threats and pressures (assisted natural regeneration); modification of these estimates based on expected site resilience, competition from invasive non-native plants and connectivity to the surrounding landscape; and where appropriate, additional risk-adjusted estimates of gain arising from the reintroduction of missing plant species or other habitat attributes (active restoration). In the absence of active restoration, the design of the Vegetation Integrity metric favours biodiversity offset sites with moderate Vegetation Integrity scores. Early evaluation of sites assessed under the Biodiversity Conservation Act 2016 suggest that offset sites are dominated by areas with moderate scores which is consistent with the intent of improving biodiversity value rather than averting future losses. Although developed within the Australian context, the new Vegetation Integrity metric has general appeal to robust, transparent and practical quantification of terrestrial biodiversity value elsewhere.